Effects of grain source and feed additive inclusion on processing characteristics and feeding value of swine diets - Friesen, Walter Garrett (My University, 2025)
A total of 7 experiments were conducted and structured in 3 chapters to evaluate the effects of grain sources and feed additive supplementation on feed processing characteristics, digestibility of energy and AA, and growth performance of growing pigs. For Chapter 1, two experiments were conducted to determine the effects of Kernza® grain on geometric mean diameter (dgw), Standard deviation (Sgw), angle of repose (AoR), and pellet durability index (PDI). Grinding characteristics were determined by changing hammermill screen hole diameters (2.0 mm, 2.8mm, 3.6mm), while pelleting characteristics were observed by increasing inclusion levels of Kernza® into treatments (0, 2.5, 5, 10, 30%). Increasing screen hole diameter increased dgw and decreased Sgw. Increasing Kernza grain from 0 to 30% of the diet improved PDI from 58.6% to 88.4%. For Chapter 2, two experiments were conducted to determine the effect of 3 sorghum varieties (red non-waxy, red waxy, white waxy) on dgw, Sgw, AoR, and PDI when ground with consistent hammermill settings (Exp.1), or to a consistent dgw of 550µm (Exp. 2). Waxy sorghum had greater dgw and PDI with a lower sgw , and AOR than that of the non-waxy sorghum and corn within Exp. 1. When comparing grain sources at a consistent particle size, waxy sorghum had a lower sgw leading to a more uniform product. Waxy red sorghum diets improved PDI compared to other grain sources. Chapter 3 encompassed three experiments to determine the impact of feed additive premix (FAP; proprietary blend of enzymes, prebiotics, plant extracts, and acidifiers) on energy metabolism, standardized ileal digestibility of AA, and growth performance when fed to pigs with varying diet compositions. Treatments were arranged with 2 levels of FAP (0.0, or 0.13%), and 3 diet types (corn-, sorghum-, sorghum & DDGS-based). Pigs fed corn and sorghum-based diets had similar growth performance and pigs fed sorghum and DDGS-based diets had reduced growth performance. The FAP used in this experiment did not improve growth performance of pigs and even reduced ADG of finishing pigs fed sorghum-based.
Keywords: Cereal source; Pellet quality; Particle size; Nutrient digestibility